2013
DOI: 10.1007/s00221-012-3378-z
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of stimulus spatial frequency-dependent contrast detection

Abstract: Psychophysical studies on human and non-human vertebrate species have shown that visual contrast sensitivity function (CSF) peaks at a certain stimulus spatial frequency and declines in both lower and higher spatial frequencies. The underlying neural substrate and mechanisms remain in debate. Here, we investigated the role of primary visual cortex (V1: area 17) in spatial frequency-dependent contrast detection in cats. Perceptual CSFs of three cats were measured using a two-alternative forced choice task. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 42 publications
1
31
0
Order By: Relevance
“…This assumption is supported by several lines of evidence. One is that, using single-unit microelectrode recording in cat V1, the psychophysical CS function (CSF) was highly correlated with the neuronal CSF (Meng et al, 2013 ). Another is that the fMRI BOLD response in humans covaries with contrast enhancement (Boynton, Demb, Glover, & Heeger, 1999 ) and SF frequency (Goodyear et al, 2000 ), with the relationship being especially tightly coupled for low-SF stimuli (Olman, Ronen, Ugurbil, & Kim, 2003 ).…”
Section: Methodsmentioning
confidence: 99%
“…This assumption is supported by several lines of evidence. One is that, using single-unit microelectrode recording in cat V1, the psychophysical CS function (CSF) was highly correlated with the neuronal CSF (Meng et al, 2013 ). Another is that the fMRI BOLD response in humans covaries with contrast enhancement (Boynton, Demb, Glover, & Heeger, 1999 ) and SF frequency (Goodyear et al, 2000 ), with the relationship being especially tightly coupled for low-SF stimuli (Olman, Ronen, Ugurbil, & Kim, 2003 ).…”
Section: Methodsmentioning
confidence: 99%
“…Four cats were used in this experiment. The recording preparations were similar to those described previously (Hua et al 2006;Hua et al 2010;Meng et al 2013;Yang et al 2016). The cats were anaesthetized with ketamine HCl (40 mg kg −1 , I.M.)…”
Section: Examination Of Tdcs-induced Neuronal Activity In A21amentioning
confidence: 99%
“…These neuronal response changes were not due to a deep anesthesia level applied in DR cats because the heart rate and ECG of DR and control cats were maintained in the same normal range during electrophysiological recording, and the mean dose of anesthetic-urethane (mg/kg body weight/hr) used in DR cats (20.5±0.70) and control cats (20.8±0.59) exhibited no significant difference (p>0.1) ( S3 Table ). Additionally, our previous investigations demonstrated that giving as much as four times the minimum level of urethane required to anesthetize cats did not alter the degree of neuronal response selectivity for stimulus orientations and motion directions nor significantly changed the visually-driven response and spontaneous activity of V1 neurons [ 24 , 37 , 38 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Each cat was prepared for acute in vivo single-unit recording after at the end of DR period. The recording procedures were similar to that described in our previous studies [ 24 , 36 38 ]. Briefly, anesthesia was induced by injection of ketamine HCl (40 mg/kg, im) and xylazine (2 mg/kg, im).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation